2021
DOI: 10.1037/ser0000394
|View full text |Cite
|
Sign up to set email alerts
|

“Day-to-day, it’s a roller coaster. It’s frustrating. It’s rewarding. It’s maddening and it’s enjoyable”: A qualitative investigation of the lived experiences of addiction counselors.

Abstract: Psychologists in medication for addiction treatment (MAT) settings routinely oversee the work of addiction counselors as supervisors, administrators, and human resource specialists. Limited research has explored the lived experiences of counselors who work in programs that have scaled-up MAT in response to the opioid crisis in the U.S. Thirty-one addiction counselors who worked in MAT programs that had scaled-up treatment capacity were interviewed about 3 facets of their lived experiences: work roles, work mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Interviewees lamented that they found recent applicants were overly concerned with pay and lacked a commitment to helping others. This relates to recent research that revealed how SUD counselors choose their profession because of intrinsic rewards and interest rather than the salary (Oberleitner et al, 2021). The interviewees in this study had similar commitments to the field when they started working so they expected new counselors to have that same passion.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Interviewees lamented that they found recent applicants were overly concerned with pay and lacked a commitment to helping others. This relates to recent research that revealed how SUD counselors choose their profession because of intrinsic rewards and interest rather than the salary (Oberleitner et al, 2021). The interviewees in this study had similar commitments to the field when they started working so they expected new counselors to have that same passion.…”
Section: Discussionmentioning
confidence: 79%
“…The perception that SUD clients are more difficult to counsel, however, may impact recruitment because new counselors are less likely to apply for positions in SUD treatment if they think the job will be more stressful and less rewarding. They may also fear being stigmatized themselves due to their association with such a highly stigmatized group (Madden, 2019; Oberleitner et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although guidance regarding disclosure highlights negative perceptions of self-relevant research (Prinstein et al, 2013), there are mental health professionals and stakeholders who hold positive perceptions of it. Several authors of commentaries and studies acknowledge the unique perspectives offered by mental health professionals with lived experience, also known as prosumers (Boyd et al, 2016; Devendorf, 2020; Kundra & Salzer, 2019; Oberleitner et al, 2021; Victor, Lewis, & Muehlenkamp, 2022). For example, people with lived experience and mental health advocates may view self-relevant researchers as having greater insight or possessing intrinsic motivation.…”
Section: What Stereotypes Are Associated With Self-relevant Research?mentioning
confidence: 99%